Des traces littéraires haïtiennes au Congo - Elisabeth Mudimbe-Boyi (Continents manuscrits)
This partial transcription of a video interview with Elisabeth Mudimbe-Boyi, critic, as well as professor emeritus of French and comparative literature at Stanford University, conducted by Jean Jonassaint in April 2020, as part of a research project on the contribution of Haitians to the creation of modern Congo, sheds light on an unusual intellectual path that does not, as is most often the case, go from South to North, but from South to South. Haiti and the Congo had, in the early years of independence, not only historical but also cultural relations. This interview looks back at these relations, which until now have been little studied, while retracing, among other things, the university milieu of the early 1960s, the role played by a non-aligned Belgian professor, and the birth of a publishing house, Mont Noir, which made courageous and sometimes futuristic editorial choices in the 1970s.